2013
DOI: 10.1021/nn403743b
|View full text |Cite
|
Sign up to set email alerts
|

Custom Cerium Oxide Nanoparticles Protect against a Free Radical Mediated Autoimmune Degenerative Disease in the Brain

Abstract: Cerium oxide nanoparticles are potent antioxidants, based on their ability to either donate or receive electrons as they alternate between the +3 and +4 valence states. The dual oxidation state of ceria has made it an ideal catalyst in industrial applications, and more recently, nanoceria's efficacy in neutralizing biologically generated free radicals has been explored in biological applications. Here, we report the in vivo characteristics of custom-synthesized cerium oxide nanoparticles (CeNPs) in an animal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
240
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(255 citation statements)
references
References 76 publications
14
240
0
1
Order By: Relevance
“…In addition; no adverse effects of nanoceria in healthy mice were observed [74]. Furthermore; recent studies with animal models show that cerium oxide nanoparticles cross the blood-brain barrier which opens a new therapeutical window in context of fighting brain diseases [71,75]. In our study; CNP was found to significantly induce cytotoxicity in astrocytoma cells in vitro; whereas the cell viability of endothelial HUVEC and HMEC-1 cells reflecting a stromal cell model was not decreased using identical concentrations.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…In addition; no adverse effects of nanoceria in healthy mice were observed [74]. Furthermore; recent studies with animal models show that cerium oxide nanoparticles cross the blood-brain barrier which opens a new therapeutical window in context of fighting brain diseases [71,75]. In our study; CNP was found to significantly induce cytotoxicity in astrocytoma cells in vitro; whereas the cell viability of endothelial HUVEC and HMEC-1 cells reflecting a stromal cell model was not decreased using identical concentrations.…”
Section: Discussionsupporting
confidence: 42%
“…One of the rather novel approaches is the use of nanoparticles; which themselves exhibit an anti-cancer activity. In studies focusing on the putative use of cerium oxide nanoparticles (CNP; nanoceria) in therapies against neurodegenerative diseases it was found; that CNP (lower than 10 nm in size) were able to pass the BBB of rodents; where they prevented neuronal decay via an antioxidant activity based on their ability to switch between the two redox-states III and IV [69][70][71]. Based on that; we investigated in a simple in vitro tumorstroma model whether redox-active cerium oxide nanoparticles (CNP; nanoceria) with a mean size of about 4.7 nm diameter modulate cell toxicity and the invasive capacity of malignant glioma and endothelial cells (ECs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Values listed under blots represent relative ratios of p-DRP1 S616 to total DRP1 protein normalized to actin nanoparticles to cross the BBB strikingly increased after injury (resulting in increased ROS/RNS). 57,58 By contrast, another study reported very small (2.9 nm diameter), citrate/ EDTA-stabilized CeO 2 nanoparticles administered intravenously to healthy rats appeared to cross the intact BBB, 56 suggesting that particle modifications might help improve neuronal delivery. In sum, considering the variability in findings to date, efficient delivery of nanoceria to neurons remains an important issue requiring further research and investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Several recent studies have addressed the ability of CeO 2 nanoparticles to cross the BBB. [56][57][58] In two of these studies, CeO 2 nanoparticles were administered intravenously and the concentration of nanoparticles was very low in the normal brain. 57,58 The study by Kim et al 57 used nanoceria that were surface modified with an artificial polymer phospholipid-polyethylene glycol, which is often added to nanoparticles to improve uptake and biodistribution, 59 yet these particles were also found only in low amounts in brain tissue.…”
Section: Discussionmentioning
confidence: 99%